A study of internet addiction among students of Sekolah Menengah Jenis Kebangsaan Pei Yuan, Kampar - Yong, Shu Qin (2011)
There are many studies about internet use and internet addiction and it is one of the things that influence our daily life. This study examines the internet addiction in secondary school. The sample consisted of 120 students in Sekolah Menengah Kebangsaan Jenis Pei Yuan Kampar, Perak. The study utilized an instrumental to measure the internet addiction; namely Internet Addiction Test (IAT). Demographic factors (age, gender and grade of level) were examined too. Data analysis included descriptive and inferential statistic (Chi-square and T-test). The result suggests that the level of internet addiction among SMJK Pei Yuan is moderate and tends to minimal. Moreover, there is a significant of gender difference in internet addiction, t (118) = 2.380, p = 0.019. However, there is no significant association between internet addiction among the lower and upper secondary students of SMJK Pei Yuan, Kampar, x 2 (1, n = 120) = 0.306. It is recommended that problem of internet addiction should be aware to prevent growing of internet addiction.